Keragaman Genetik Kelapa Dalam Bali (DBI) dan Dalam Sawarna (DSA) Berdasarkan Penanda Random Amplified Polimorphic DNA (RAPD) - DONATA S. PANDIN (Pusat Penelitian dan Pengembangan Perkebunan, 2009)
Genetic Diversity of Bali Tall (DBI) and Sawarna Tall (DSA) based onRandom Amplified Polymorphic DNA (RAPD)Genetic Diversity of Bali Tall (DBI) and Sawarna Tall (DSA) based on Random Amplified Polymorphic DNA (RAPD). Ten Plants were used in each population. The objective of this research were to determine genetic diversity within- and inter-population of Bali Tall (DBI) and Sawarna Tall (DSA) coconuts, and genetic relationship of those population based on RAPD ( ). Research was done in Plant Biology Laboratory of CenterResearch of Genetic Resources and Biotechnology, Institut Pertanian Bogor, February – May 2007. DNA extraction was done by modified Rohde method and to determine the concentration and quality of DNA by Sambrook method. Ten RAPD 10-mer were used namely OPA-02, OPA-08, OPA-10, OPA-13, OPA-20, OPB-08, OPB-11, OPB-12, OPB-15, OPB-20. Genetic relationship between individuals of DBI and DSA coconut populations based on NTSys ver.2.0 programe (Program Numerical Taxonomy and Multivariate Analysis), and clustering analysis based on UPGMA method. These ten RAPD primers used could separate DBI and DSA in each group. Genetic diversity within-population of Bali Tall coconut population range from 2.4% to 30.7% with average 21.7%. So that, opportunity to improve characters in DBI coconut population could be done by selection. Genetic diversity within-population of Sawarna Tall coconut population progressively narrow, range from 1.5% to 12.4% with average 12.7%, so that selection in order to character improvement in this population could be done selectively. Genetic relationship between DBI dan DSA populations far enough (54%), so that crossing between those population will be good for characters improving.